2016
DOI: 10.1186/s12903-016-0234-8
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries risk indicators in early childhood and their association with caries polarization in adolescence: a cross-sectional study

Abstract: BackgroundBased on the hypothesis that biological and social risks accumulate during life, it is important to identify possible dental caries risk indicators from the life course of early childhood and assess their association with caries polarization in adolescence.MethodsA cross-sectional design was applied to the study, and a multistage cluster sampling method used to draw a representative sample of 1063 18-year-old Lithuanian adolescents. The dental examinations were performed according to the methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…The microbial community becomes more diverse over the first several years of life and continues to vary through the development of teeth, and finally become stable around adulthood 16 18 . Early oral microbiota development has a significant impact on oral health and diseases in adulthood 19 . Understanding the oral microbiota difference in children in different ethnicities including the ethnic minority will allow us to gain deep insight into the factors that might drive oral health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…The microbial community becomes more diverse over the first several years of life and continues to vary through the development of teeth, and finally become stable around adulthood 16 18 . Early oral microbiota development has a significant impact on oral health and diseases in adulthood 19 . Understanding the oral microbiota difference in children in different ethnicities including the ethnic minority will allow us to gain deep insight into the factors that might drive oral health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Like data described in other studies, [ 47 , 48 ] girls in the present investigation (n = 40) had a mean dmft of 1.87, whereas the boys had a much higher index (2.83). This association may be due to socio-cultural and psychosocial factors, as previous studies report greater awareness and self-care among the female sex, [ 49 52 ] although the studies cited involved adolescents.…”
Section: Discussionmentioning
confidence: 95%
“…To address the significantly greater burden of dental caries in this population it is important to investigate risk indicators for caries to inform prevention and health promotion policies and interventions. Whilst many studies show that the strongest predictor of future caries is past caries experience [18], a recent comprehensive review [19] has shown that the utility of biological caries risk predictors differ between countries. Remote Indigenous communities in Australia may have a different mix of risk indicators than elsewhere in Australia, and these may have aspects in common with other Indigenous communities around the world.…”
Section: Introductionmentioning
confidence: 99%